2022
DOI: 10.3390/diagnostics12010168
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous CT-Guided Biopsy of the Craniovertebral Junction: Safety, Diagnostic Yield, and Technical Notes

Abstract: The craniovertebral junction defined as the occiput, the atlas, and the axis is a complex bony region that contains vital neural and vascular structures. We report the experience of a single academic institution regarding CT-guided biopsy of this skeletal region. We reviewed all of the CT-guided biopsies performed in our department, completed in the craniovertebral junction. We collected data in regard to biopsy procedures, patients’ vital statistics, and histopathological diagnosis. In total, 16 patients (8M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…CT guidance, with the aid of intravenous contrast media injection for the visualization of vertebral arteries if necessary, has been proven to be feasible and safe even in this complex skeletal region (Figure 4). Spinnato et al in 2022 reported the feasibility and safety of CT-guided bone biopsies performed in the craniovertebral junction of 16 patients, with a diagnostic accuracy of 81.3% [28]. In this series, the needle approach was always posterior or lateral, but it is well known that in peculiar atlantoaxial spinal locations (e.g., dens of the atlas), an anterior open-mouth approach through the oropharyngeal space should be chosen [29,30].…”
Section: Skull Base and Craniovertebral Junction (C0-c2)mentioning
confidence: 92%
See 2 more Smart Citations
“…CT guidance, with the aid of intravenous contrast media injection for the visualization of vertebral arteries if necessary, has been proven to be feasible and safe even in this complex skeletal region (Figure 4). Spinnato et al in 2022 reported the feasibility and safety of CT-guided bone biopsies performed in the craniovertebral junction of 16 patients, with a diagnostic accuracy of 81.3% [28]. In this series, the needle approach was always posterior or lateral, but it is well known that in peculiar atlantoaxial spinal locations (e.g., dens of the atlas), an anterior open-mouth approach through the oropharyngeal space should be chosen [29,30].…”
Section: Skull Base and Craniovertebral Junction (C0-c2)mentioning
confidence: 92%
“…Spinnato et al in 2022 reported the feasibility and safety of CT-guided bone biopsies performed in the craniovertebral junction of 16 patients, with a diagnostic accuracy of 81.3% [28]. In this series, the needle approach was always posterior or lateral, but it is well known that in peculiar atlantoaxial spinal locations (e.g., dens of the atlas), an anterior open-mouth approach through the oropharyngeal space should be chosen [29,30].…”
Section: The Spinementioning
confidence: 92%
See 1 more Smart Citation
“…The anterior skull base proper is formed medially by the cribriform plate, which forms the roof of the nasal cavity; laterally, by the orbital plates of the frontal bone, which form the roof of the orbits and ethmoid air cells; and posteriorly, by the planum sphenoidale and lesser wings of the sphenoid. Percutaneous image-guided biopsy for definitive histologic diagnosis was achieved in 86% (12/14) of cases in the skull [12] and 81.3% (13/16) of cases in the craniovertebral junction [13]. However, for 'central' skull base tumors, image-guided biopsy is not safe due to the presence of the vital adjacent structures described above.…”
Section: Introductionmentioning
confidence: 99%
“…This can be useful, particularly for atypical cases. CT-guidance was demonstrated to be safe and effective for interventional procedures in almost all skeletal sites, including the riskiest and most delicate ones, such as the craniovertebral junction (C0–C3) or the skull [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%